PERAN HUMAS DALAM PROSES SOSIALISASI PROGRAM BEASISWA BAZNAS KEPADA MAHASISWA UNIVERSITAS ISLAM NEGERI SUMATERA UTARA MEDAN - Nur Cahaya; Muhammad Husni Ritonga; Muhammad Jailani (JURNAL PURNAMA BERAZAM, 2022)
ABSTRACT This study aims to find out how the role of public relations in the process of socializing the BAZNAS scholarship program, the supporting and inhibiting factors of public relations in the process of socializing the BAZNAS scholarship program, and the results achieved in the scholarship socialization process. This research is a qualitative descriptive study. Research informants in this study were the Head of Public Relations, Vice Chancellors III, IV, KTU, BAZNAS UIN SU Scholarship Coordinator, and BAZNAS UIN SU scholarship recipients. Data collection techniques using observation, interviews and documentation. The data analysis technique is interactive analysis with the following stages: data reduction, data presentation and conclusion drawing. The data validity technique used is the source triangulation technique. The results showed that the role of Public Relations in the process of socializing the BAZNAS scholarship program to UIN SU students, namely: 1) the role of Public Relations in the process of socializing the BAZNAS scholarship program as a form of contribution built by Public Relations to socialize the scholarship program 2) supporting factors for the role of Public Relations, namely the support from superiors , PR barriers are the lack of external data and information, the lack of skilled human resources in their fields 3) The results achieved by Public Relations in the process of socializing the BAZNAS scholarship program to UIN SU students are the role of Public Relations of UIN SU as a relationship builder, the role of Public Relations as a facilitator, the role of PR to meet the information needs of scholarships for UIN SU students. Keywords: Role, Public Relations, BAZNAS Scholarship